Age and growth of the Critically Endangered flapper skate, Dipturus intermedius. Issue 9 (28th June 2021) - Régnier, Thomas; Dodd, Jane; Benjamins, Steven; Gibb, Fiona M.; Wright, Peter J.
Abstract: Knowledge of vital data such as growth and age at maturity is necessary to develop effective management strategies for endangered species. The Critically Endangered flapper skate ( Dipturus intermedius ) is the largest skate in the North Atlantic and growth information, necessary to assess key life‐history traits, populations' growth rates and anticipate their response to management measures, is still lacking. While classical age estimation methods used in fish generally require the analysis of calcified structures, destructive methods are incompatible with conservation objectives for this species. Taking advantage of the high recreational value of the flapper skate, this study uses citizen‐science data originating from photo‐identification of trophy pictures and tag–recapture data supported by anglers to estimate growth in this Critically Endangered species. Using the growth increments measured between recapture events, an individual‐based Von Bertalanffy growth model was fitted to the data using Bayesian inference. The results confirm that the flapper skate is a long‐lived species with ages estimated as >40 years for the largest individuals captured. Despite this longevity, the model reveals a relatively fast initial growth but relatively late ages at maturity and significant sex‐related differences in both growth rate and maximum size. These results suggest that population growth rate, and therefore recovery, might be much slower than previously reported. By using citizen science this study provides the necessary information to begin understanding population dynamics and monitor the recovery of an iconic Critically Endangered species.